Potts shunt as an effective palliation for patients with end stage pulmonary arterial hypertension - Bobhate, Prashant (Indian Heart J, 2021)
BACKGROUND: Potts shunt has been suggested as an effective palliative therapy for patients with pulmonary artery hypertension (PAH) not associated with congenital heart disease. MATERIALS AND METHODS: This is a prospective single-center study performed to assess outcomes of Potts shunt in patients with PAH who are in functional class III or IV. RESULTS: 52 patients in functional class III/IV with pulmonary arterial hypertension without significant intra or extracardiac shunt on maximal medical therapy were evaluated and counseled for undergoing Potts shunt/patent ductus arteriosus (PDA) stenting. 16/52 patients (13 females) consented for the procedure; 14 patients underwent surgical creation of Potts, and 2 underwent transcatheter stenting of PDA, which physiologically acted like a Potts shunt. Standard medical therapy was continued in patients who did not consent for the procedure. 12/16 patients survived the procedure. Patients who did not survive the procedure were older, with severe right ventricular systolic dysfunction, and functional class IV. Patients who survived the procedure were followed up in the pulmonary hypertension clinic. The Median follow-up was 17 months (1–40 months). 11/13 patients discharged after the operation showed sustained clinical, echocardiographic, and biochemical improvement, which reduced need for pulmonary vasodilator therapy in 10/13 patients. There was one death in the follow-up period 16 months post-surgery due to lower respiratory tract infection. CONCLUSION: Potts shunt is feasible in patients with PAH without significant intra or extracardiac shunts. It can be done safely with an acceptable success rate. Patient selection, preoperative stabilization, and meticulous postoperative management are essential. It should be performed at the earliest sign of clinical, echocardiographic, or laboratory deterioation for optimal outcomes. Long-term follow-up is required to see a sustained improvement in functional class and the need for a lung transplant in the future.